Multi-Layer QCA Reversible Full Adder-Subtractor Using Reversible Gates for Reliable Information Transfer and Minimal Power Dissipation on Universal Quantum Computer - Jun-Cheol Jeon (Applied Sciences, 2024)
The effects of quantum mechanics dominate nanoscale devices, where Moore’s law no longer holds true. Additionally, with the recent rapid development of quantum computers, the development of reversible gates to overcome the problems of energy and information loss and the nano-level quantum-dot cellular automata (QCA) technology to efficiently implement them are in the spotlight. In this study, a full adder-subtractor, a core operation of the arithmetic and logic unit (ALU), the most important hardware device in computer operations, is implemented as a circuit capable of reversible operation using QCA-based reversible gates. The proposed circuit consists of one reversible QCA gate and two Feynman gates and is designed as a multi-layer structure for efficient use of area and minimization of delay. The proposed circuit is tested on QCADesigner 2.0.3 and QCADesigner-E 2.2 and shows the best performance and lowest energy dissipation. In particular, it shows tremendous improvement rates of 180% and 562% in two representative standard design cost indicators compared to the best existing studies, and also shows the highest circuit average output polarization.